Proposed special active vocabulary list in Pilipino for grade-one Hiligaynon speakers - Aguirre, Angelina Ferraris 1925- (s.n.], 1971)
This paper is concerned chiefly with evolving a special active vocabulary list in Pilipino for Grade I Hiligaynon speakers and how these vocabulary items are to be graded as to the level of difficulty through contrastive analysis. The result of this study will provide Hiligaynon teachers with a list of functional vocabulary with which to start their language teaching. It will also help them to determine which vocabulary items should be taught first, which items need more drills, and which ones are to be evaluated on the basis of ease and difficulty. The list will also help textbook writers in the preparation of pre-primers and primers because the words were culled from the actual utterances of seven-year old children and are psychologically arranged from the easiest to the most difficult.